Assessment of Infection Prevention and Control Program in Misurata Medical Center Using the WHO Infection Prevention and Control Assessment Framework (IPCAF), 2023. - Azzain, Alyaa (Khalij-Libya Journal of Dental and Medical Research, 2024)
Globally, about 5–15% of patients admitted to hospitals get HAIs and the primary cause for this is poor infection prevention and control (IPC) practices in the hospitals. HAIs continue to be one of the most common adverse events in health care, Despite the developments in infection control measures, HAIs play crucial role in occurrence of antimicrobial resistance. This study aims to evaluate the IPC compliance at Misurata Medical Center (MMC), using the WHO IPCAF tool. A hospital based cross sectional study conducted in The Central Misurata Center in August 2023, data was collected using IPCAF tool form WHO by interviewing the IPC specialist in the center. Responses were scored and interpreted according to WHO guidelines. The total score was calculated to be 607.5 which according to the IPCAF Scoring and Interpretation is an advanced level (601-800), meaning full implementation of the IPC core components according to the WHO recommendations and appropriate to the facility`s needs. Structures and processes of Infection prevention and control (IPC) are in general well established in Misurata Central center. Regular assessment of IPC activities is needed and better action plans to improve the IPC activities in the MMC should be adopted. على الصعيد العالمي، يصاب حوالي 5-15% من المرضى الذين يتم إدخالهم إلى المستشفيات بعدوى المستشفيات ، والسبب الرئيسي لهذا هو ضعف ممارسات الوقاية من العدوى ومكافحتها. تستمر عدوى المستشفيات في كونها واحدة من أكثر الأحداث السلبية شيوعًا في الرعاية الصحية، وعلى الرغم من التطورات في تدابير مكافحة العدوى، فإن عدوى المستشفيات تلعب دورًا هاما في حدوث مقاومة المضادات الميكروبية. تهدف هذه الدراسة إلى تقييم الامتثال لممارسات الوقاية من العدوى ومكافحتها في مركز مصراتة الطبي (MMC)، باستخدام أداة IPCAF التابعة لمنظمة الصحة العالمية. دراسة مقطعية أجريت في مركز مصراتة المركزي في أغسطس 2023، تم جمع البيانات باستخدام أداة IPCAF من منظمة الصحة العالمية من خلال مقابلة أخصائي الوقاية من العدوى في المركز. تم تسجيل الاجابات وتفسيرها وفقًا لإرشادات منظمة الصحة العالمية. تم حساب النتيجة الإجمالية لتكون 612.5، والتي وفقًا لتفسير وتسجيل IPCAF تعتبر مستوى متقدمًا (601-800)، مما يعني التنفيذ الكامل لمكونات الوقاية من العدوى الأساسية وفقًا لتوصيات منظمة الصحة العالمية وبما يتناسب مع احتياجات المؤسسة. الهياكل والعمليات الخاصة بمكافحة العدوى والوقاية منها (IPC) مُتأسسة بشكل عام في مركز مصراتة المركزي. هناك حاجة لتقييم منتظم لأنشطة الوقاية من العدوى واعتماد خطط عمل أفضل لتحسين أنشطة الوقاية من العدوى في مركز مصراتة الطبي